EVALUATION OF BODY COMPOSITION IN ELDERS OF BOTH GENDER (Fiep Bulletin - online, 2020)
Introduction: The increase of elders on Brazilian population enticed a discussion about life quality and degenerative diseases among this population. Objective: Evaluate the physical composition of elders who were put on a physical activity program at the city of Guarulhos. Materials and methodology: The population studied were elders over 60 years old, being 450 woman and 46 men, totaling 496 subjects who exercised twice a week. The anthropometric variables from the physical composition evaluated were the BMI (body mass index), waist circumference (WC), waist-hip ratio (WHR) and bodyfat percentage (BF%). Results: Regarding BMI, females had the worst scores, being 34% obese and men with 26% obese. The CC test found that women had the worst result with 50% of the elderly women at very high risk and men with 24%. Comparing females with males on the RCQ test, it showed the worst outcome for women with 34% classified at very high risk and men with 29%. In the% CG test comparing genders, men showed the worst score with 60% classified as inappropriate and women obtained 55%, presenting a risk of acquiring chronic degenerative pathologies. Conclusion: Females had the worst scores and body fat was more localized in the abdominal region, being the anatomical site that indicates the greater susceptibility of these elderly women to chronic non-transmissible degenerative diseases.